Bio-inspired gallic acid-gelatin coating: A novel strategy for eco-friendly interfacial modification of carbon fiber composites. (August 2021) - Zhang, Mengjie; Jin, Lin; Zhai, Yuanyuan; Cheng, Chunxia; Yan, Fei; Liu, Yu; Liu, Liu; Ao, Yuhui
Abstract: The weak interfacial adhesion between carbon fiber (CF) and resin matrix are the main factors limiting the performance of CF reinforced polymer composites. Therefore, it was necessary to modify the surface of CF, but most processes also confronted the problems of unsustainable and environmental pollution. Here, the eco-friendly bio-based gallic acid (GA) and gelatin (GE) were biomimetic co-deposited on the CF surface in aqueous solution. The co-depositing GA-GE coating adhered well to the surface of inert CF and significantly increased CF surface active functional groups and wettability, resulted in the interfacial shear strength increased by 78.7%, compared to the pristine CF/epoxy composites. Hence, it is a promising approach to significantly enhance the interfacial adhesion of CF/epoxy composites and expected to be used in industrial production. Highlights: ∙The raw materials used in this process are green and sustainable. ∙This method was completed in a mild aqueous solution, without using toxic reagents. ∙A bio-inspired phenol-amine coating was introduced on the interface of CF composites. ∙The co-depositing GA-GE coating significantly increased interfacial properties of composites.